Dukungan Sosial dan Self-Efficacy Karyawan di PT. X - Carmella Josephine; Sutarto Wijono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The high demands for efficiency, innovation, and fierce competition in the flexible packaging industry require PT. X employees to have strong self-efficacy, supported by a supportive work environment. This study aims to determine the relationship between social support and self-efficacy among PT. X employees. This study uses a quantitative approach with a correlational design and involves 105 PT. X employees who have worked full-time for at least 1-2 years. The hypothesis test results show a significance value of 0.000 with a positive correlation coefficient of 0.406, which means that there is a positive and significant relationship between social support and self-efficacy among PT. X employees. The higher the social support received, the higher the employees’ self-efficacy. Social support contributes effectively by 24.9% to self-efficacy. The results of this study indicate that social support is an important predictor of self-efficacy and provide practical implications for PT. X to invest in and develop a supportive work culture to improve the psychological capital and performance of employees.